A Systematic Review of Cutaneous Dog Ear Deformity: A Management Algorithm - Kang, Ajaipal S.; Kang, Kevin S. (Plastic and reconstructive surgery. Global open, 2020)
BACKGROUND:Dog ear, a characteristic bunching up of excess tissue formed during wound closure, is a common unsightly problem in cutaneous surgery. It may present as a cosmetic concern or a source of physical discomfort. Several management techniques have been reported, but it is unclear which approach is the most effective or whether outcomes vary with surgical situations. This report assesses the best practices for dog ear management. METHODS:A systematic literature search was performed. All relevant articles written in English and involving human subjects were included. RESULTS:There were 2028 potentially relevant articles, but only 36 articles met the inclusion criteria. These articles were published in multispecialty journals. They included 23 techniques or case report articles, 6 retrospective and prospective studies, but no clinical trial or randomized control trial. Ten major techniques were identified in the literature. No single technique was proved to be superior in the literature. There was no recommended algorithm in the literature. CONCLUSIONS:Despite there being no single recommended technique to manage dog ear deformities, there is ample evidence to suggest surgeons avoid a pre-planned elliptical design, use a proper skin-conserving design for excision, and carry out a meticulous suture closure as the first steps to prevent dog ears. We discuss the indications for each of the ten techniques and propose an algorithm for dog ear management. Until further research is performed, multispecialty cutaneous surgeons should familiarize themselves with the discussed techniques to provide patients with the best functional and aesthetic results.